Evaluating the Protective Role of Rutin Against Azithromycin-Induced Hepatorenal Histopathological Changes in Albino Rats: Rutin Hepatorenal Protective Role - Reem Abdul Raheem Mirdan Alsaad; Mariam Mohammed Burhan; Hameda Abd Al-Mhdi Ghazi; Hussein Abbas Selman; Rashid, Ahmed Ibraheem (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Azithromycin, a widely used macrolide antibiotic, is associated with dose-dependent hepatorenal toxicity primarily mediated by oxidative stress and inflammation. Rutin, a natural flavonoid, possesses potent antioxidant and anti-inflammatory properties that can mitigate organ damage. This study aimed to evaluate the potential of Rutin to ameliorate azithromycin-induced histopathological alterations in the livers and kidneys of albino rats. Methods: Thirty-six adult male albino rats (180–200 g) were allocated into five groups: a control group (normal saline), groups receiving azithromycin (30 mg/kg) for 7 (T1) or 14 days (T2), and groups receiving concurrent azithromycin and rutin (50 mg/kg) for 7 (T3) or 14 days (T4). After the treatment period, liver and kidney tissues (one kidney per animal) were harvested for histopathological examination using hematoxylin and eosin (H&E) staining. Results: Azithromycin administration induced a significant time-dependent histopathological damage. The T2 group (14-day azithromycin treatment) exhibited severe hepatic injury, including hepatocellular necrosis, sinusoidal dilatation, and inflammatory infiltration, as well as renal damage characterized by glomerular atrophy and tubular necrosis. Cotreatment with Rutin markedly attenuated these effects. The T4 group (14-day cotreatment) showed near-complete preservation of the hepatic architecture and renal histology, with minimal signs of inflammation and cellular damage. Conclusion: Co-administration of Rutin confers significant protection against azithromycin-induced hepatorenal damage, attributed to its antioxidative and anti-inflammatory mechanisms. These findings highlight the potential of Rutin as an effective adjuvant therapy to minimize antibiotic-associated organ toxicity.